2006
DOI: 10.1002/ejic.200600477
|View full text |Cite
|
Sign up to set email alerts
|

New Dimeric Copper(II) Complex [Cu(5‐MeOsal)2(μ‐nia)(H2O)]2 with Magnetic Exchange Interactions through H‐Bonds

Abstract: The synthesis and characterization (elemental analysis, IR, electronic and EPR spectra as well as magnetization measurements over the temperature range 1.8 K-300 K) of solid complex [Cu(5-MeOsal) 2 (µ-nia)(H 2 O)] 2 (1; 5-MeOsal = 5-methoxysalicylate, nia = nicotinamide) is reported together with the crystal structure. In blue-green complex 1, two Cu(5-MeOsal) 2 (H 2 O) units are held together by a pair of bidentate nonchelating nicotinamide ligands, which form a (CuNC 3 O) 2 ring. Each Cu atom adopts a distor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 23 publications
2
24
1
Order By: Relevance
“…It has been suggested that the active form of ASPIRIN is, in fact, a copper complex formed in vivo [11]. A substantial effort has been devoted to the synthesis and study of solid copper(II)-salicylato complexes in our laboratories as well [12][13][14][15][16][17][18][19], bearing in mind, however, that both the copper(II) ions and the active organic molecules act in the cell, i.e. in 0162-0134/$ -see front matter Ó 2007 Elsevier Inc. All solution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the active form of ASPIRIN is, in fact, a copper complex formed in vivo [11]. A substantial effort has been devoted to the synthesis and study of solid copper(II)-salicylato complexes in our laboratories as well [12][13][14][15][16][17][18][19], bearing in mind, however, that both the copper(II) ions and the active organic molecules act in the cell, i.e. in 0162-0134/$ -see front matter Ó 2007 Elsevier Inc. All solution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has ben reported that magnetic exchange interactions through hydrogen bonds are also possible [17]. Because of the diversity of the inorganic networks and their complexity, metal carboxylate frameworks show different and usually extremely complicated magnetic behavior [16].…”
Section: Introductionmentioning
confidence: 99%
“…3) and c g ···c g distance (Janiak, 2000) is 4.17 Å. The similar supramolecular synthons R 2 2 (10) and R 2 2 (12) (Bernstein et al, 1995) have been also observed in crystal structure of one dinuclear complex (Valigura et al, 2006) and several polymeric complexes (Abourahma et al, 2002;Burrows et al, 2008;Cao et al, 2008;Korabik et al, 2011;Maharramov et al, 2012;Vaskova et al, 2011;Xu et al, 2007;Yamada et al, 1998). The crystal packing of 1 is shown in Fig.…”
Section: Resultsmentioning
confidence: 69%